High-strength fine-grained concrete based on natural zeolite (Международный научный журнал «Инженер», 2026)
The results of studying the natural zeolite from the Beltau deposit are presented. To determine the comparativerelationship between the characteristics of natural zeolite obtained from the Beltau deposit and mineral additivesin the Uzbekistan construction materials market, natural zeolitic marl, microsilica, and metakaolin from theBeltau deposit were used. It was established that the W/T ratio of the studied powders increases in the followingsequence: Beltau zeolite, crushed sand, microsilica, zeolite-containing marl, and metakaolin. Based on therheological parameters of water-mineral pastes, the yield stress was calculated, and their plasticizing sensitivityto solvents of various chemical natures was determined. It was found that the pozzolanic activity of naturalzeolite for CaO absorption is equal to 510 g/l; a change in the pH of the hydrating zeolite-cement suspensionwas observed, with its value decreasing to 12.7. Fine-grained cement concretes with strengths ranging from 75to 86 MPa were obtained using natural zeolite from the Beltau deposit at concentrations of 5 and 10%.